Diagnosis and treatment of early and locally advanced non-small-cell lung cancer: The 2019 AIOM (Italian Association of Medical Oncology) clinical practice guidelines. (April 2020) - Passiglia, F.; Bertolaccini, L.; Del Re, M.; Facchinetti, F.; Ferrara, R.; Franchina, T.; Malapelle, U.; Menis, J.; Passaro, A.; Pilotto, S.; Ramella, S.; Rossi, G.; et al.
Abstract: The Italian Association of Medical Oncology (AIOM) has developed clinical practice guidelines for the diagnosis and treatment of patients with early and locally advanced non-small cell lung cancer. In the current paper a panel of AIOM experts in the field of thoracic malignancies discussed these topics, analyzing available scientific evidences, with the final aim of providing a summary of clinical recommendations, which may guide physicians in their current practice.